2017
DOI: 10.24925/turjaf.v5i5.507-517.1077
|View full text |Cite
|
Sign up to set email alerts
|

Origin Determination and Differentiation of Gelatin Species of Bovine, Porcine, and Piscine through Analytical Methods

Abstract: Gelatin origin determination has been a crucial issue with respect to religion and health concerns. It is necessary to analyze the origin of gelatin with reliable methods to ensure not only consumer choices but also safety and legal requirements such as labeling. There are many analytical methods developed for detection and/or quantification of gelatin from different sources including bovine, porcine and piscine. These analytical methods can be divided into physicochemical, chromatographic, immunochemical, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Up to now, various studies were performed in order to detect the source of gelatin. Generally, polymerase chain reaction (PCR) based, electrophoretic, chromatographic and spectroscopic techniques were used (Eryılmaz et al, 2017). Previous studies have provided important information on determination of gelatin source both in the raw state and as an ingredient in the foodstuffs.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, various studies were performed in order to detect the source of gelatin. Generally, polymerase chain reaction (PCR) based, electrophoretic, chromatographic and spectroscopic techniques were used (Eryılmaz et al, 2017). Previous studies have provided important information on determination of gelatin source both in the raw state and as an ingredient in the foodstuffs.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence alignment analysis showed that the amino acid sequence of type I collagen between cattle and pigs was not identical. Appropriate data analysis methods can help obtain results regarding authentication or counterfeiting of gelatin ingredients in a product [11]. Identification of gelatin raw materials can use several methods.…”
Section: Introductionmentioning
confidence: 99%
“…The method of chemical precipitation on gelatin from bovine bone and pork skin that accelerates hydroxyapatite transformation (HAP) was applied to differentiate gelatin sources [12]. This method did not succeed in distinguishing the origin of gelatin in processed products, so further studies on the resulting data are needed [11]. Research by Nemati et al [13] identified amino acid content using Principal Component Analysis (PCA) with HPLC to distinguish beef and pork gelatin in products containing gelatin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations